2011
DOI: 10.1016/j.biochi.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

PKCdelta is a positive regulator of chondrogenesis in chicken high density micromass cell cultures

Abstract: a b s t r a c tWe aimed to elucidate the role of the Ca-independent PKC isoenzyme PKCdelta in the regulation of spontaneous in vitro chondrogenesis occurring in a 6-day-long culturing period in chicken limb budderived high density cell cultures (HDC). PKCdelta expression and activity were detectable throughout the entire culturing period with a peak on days 2 and 3, when most of the chondroblasts differentiate. To inhibit the activity of PKCdelta, either the natural compound rottlerin was transiently applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
2
10
1
Order By: Relevance
“…The three MAPK pathways contribute to the regulation of chondrogenesis to a various extent: while JNKs seem not to be involved in this process, p38s and ERKs are key regulators of chondrogenic differentiation; in chicken HDC, an opposing role of p38 and ERK has been reported: while the p38 MAPK pathway promotes, activation of the MEK/ERK pathway represses in vitro chondrogenesis (31). The results of our laboratory also confirmed the negative role of the ERK1/2 pathway in the regulation of in vitro chondrogenesis in the same model (22,32).…”
Section: Chondrogenesis Is Regulated By Interplay Between Numerous Insupporting
confidence: 78%
“…The three MAPK pathways contribute to the regulation of chondrogenesis to a various extent: while JNKs seem not to be involved in this process, p38s and ERKs are key regulators of chondrogenic differentiation; in chicken HDC, an opposing role of p38 and ERK has been reported: while the p38 MAPK pathway promotes, activation of the MEK/ERK pathway represses in vitro chondrogenesis (31). The results of our laboratory also confirmed the negative role of the ERK1/2 pathway in the regulation of in vitro chondrogenesis in the same model (22,32).…”
Section: Chondrogenesis Is Regulated By Interplay Between Numerous Insupporting
confidence: 78%
“…Total cell lysates for Western blot analyses were prepared as previously described [30]. 40 μg protein was separated in 7.5% SDS-polyacrylamide gels for the detection of Sox9, P-Sox9, HAS2, HAS3, CREB, P-CREB, PKA Cα, PP2A/C, aggrecan and GAPDH.…”
Section: Sds-page and Western Blot Analysismentioning
confidence: 99%
“…In this regard, an emblematic example of convergent but independent effects of Rottlerin and PKC δ downregulation is the recent study by Matta et al [16] performed in chicken chondrogenic mesenchymal cells. The authors found that both PKC δ silencing and 2.5–10  μ M Rottlerin (Sigma) decreased the protein levels of Sox9, the major cartilage-specific transcription factor, and impaired cartilage matrix production.…”
Section: Rottlerin Usage: the Open Debate On Selectivitymentioning
confidence: 99%